THE THEORY OF EDUCATIONAL TECHNOLOGY Towards a Dialogic Foundation for Design - Wegerif, Rupert; Major, Louis (Routledge, 2024)
Educational technology is controversial - some see it as essential to providing free global learning, others view it as a dangerous distraction that undermines good education. In both instances, most theories that have previously been applied to educational technology do not account for the distinctive nature and vast potential of technology. This book addresses this issue, exploring how education has been bound up with technology from the beginning, and recognising that educational aims have already been shaped by technologies. Offering a 'dialogic' theory of educational technology, Rupert Wegerif and Louis Major respond to contemporary challenges to education within this book, including, but not limited to, climate change, misinformation on the internet and the impact of Artificial Intelligence (AI). Chapters introduce, discuss, and contextualise key theories and illustrate through case studies their uses within a diverse range of educational contexts, spanning from primary education to adult lifelong learning. Each chapter also concludes with a short summary, demonstrating how these theories translate to practical implications for design. A fascinating response to current developments in educational technology, this is a crucial read for all involved in creating, researching, or making decisions about the use of technologies within educational contexts.